FROM SELECTION TO PROPOSITION: Qualitative Data Analysis Models and Methods - Wijaya, Bambang Sukma (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2015)
This article formulates the qualitative data analysis process steps to make it easier for researchers to process and interpret data systematically. The qualitative data analysis model starts from the Selection stage, which selects and sorts relevant and significant data according to the research objectives, then Categorization, which is to group important and meaningful findings into categories and sub-categories. Next is Validation, including intersubjectivity or triangulation for field research by comparing data subjects with one another and looking for links between their meanings. Meanwhile, for textual studies, validation is done by the intertextuality method, inter-context, and interdiscursivity. The next stage of data analysis is Theorization, in which the researcher interprets and dialogues important and meaningful findings with relevant concepts, theories, and previous studies. The final stage is the Proposition, in which researchers formulate new concepts, models, and theories related to the issue being studied. Although this stage is not linear, in the sense that each stage can jump back and forth according to the needs of the analysis, but researchers need to ensure that each stage is passed systematically and reliably.   DARI SELEKSI KE PROPOSISI: Metode dan Model Analisis Data Kualitatif Artikel ini merumuskan langkah-langkah proses analisis data kualitatif untuk memudahkan peneliti dalam mengolah dan menafsirkan data secara sistematis. Model analisis data kualitatif dimulai dari tahap Seleksi, yaitu memilih dan memilah data yang relevan dan signifikan sesuai dengan tujuan penelitian, kemudian Kategorisasi, yaitu mengelompokkan temuan penting dan bermakna ke dalam kategori dan subkategori. Selanjutnya adalah Validasi, termasuk intersubjektivitas atau triangulasi untuk penelitian lapangan dengan cara membandingkan subjek data satu sama lain dan mencari keterkaitan antara maknanya. Sedangkan untuk studi tekstual, validasi dilakukan dengan metode intertekstualitas, interkonteks, dan interdiskursif. Tahap analisis data selanjutnya adalah Teorisasi, di mana peneliti menginterpretasikan dan berdialog tentang temuan-temuan penting dan bermakna dengan konsep, teori, dan kajian sebelumnya yang relevan. Tahap terakhir adalah Proposisi, dimana peneliti merumuskan konsep, model, dan teori baru yang berkaitan dengan masalah yang diteliti. Walaupun tahapan ini tidak linier, dalam artian setiap tahapan dapat meloncat maju mundur sesuai kebutuhan analisis, namun peneliti perlu memastikan bahwa setiap tahapan dilalui secara sistematis dan terpercaya. To cite this article (7th APA style):Wijaya, B. S. (2015). From Selection to Proposition: Qualitative Data Analysis Models and Methods. Journal Communication Spectrum, 5(1), 1-12